Enhancing Reactivity and Selectivity of H2-driven Copper Hydride Chemistry with Bifunctional N-heterocyclic Carbene Ligands Bearing Basic Subunits - Pal, Giriraj; Voigtländer, Maximilian; Tzaras, Dimitrios-Ioannis; Gorai, Mahadeb; Teichert, Johannes F. (Synlett, 2025)
This synpacts article highlights two recent developments in H2-driven copper hydride chemistry with bifunctional N-heterocyclic carbene (NHC) ligands. Two distinct bifunctional copper(I) complexes emerge, each with different, basic nitrogen-based, catalytically active functional groups. A guanidine-appended NHC enables a site-selective catalytic hydrogenation of the so-called “privileged” amides in the presence of other, structurally closely related amides. Furthermore, a second bifunctional NHC ligand bearing a basic 2-iminopyridine subunit allows for catalytic hydrogenation of alkynes and conjugated amides under low H2 pressure. Both catalysts are placed into a common context by discussing the fundamental mechanism of heterolytic H2 activation and the fate of the resulting proton.
Keywords: N-heterocyclic carbenes; Copper; Hydrogen; Catalysis; Organocatalysis; Hydrogenation; Coordination chemistry